Design and analysis of an electro-mechanical impact sensor with an all-ways action mechanism and a Hall sensor: impact sensor with all-ways action mechanism - Bui, Xuan Son; Do, Van Gion; Pham, Duc Hung (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: The paper proposes an electro-mechanical impact sensor for grenade detonation using an all-ways action mechanism with permanent magnets and a Hall sensor. After experimental validation, a mathematical model assesses how structural parameters, such as activation threshold, inertial mass, and Hall sensor placement, affect the fuze’s sensitivity. The study provides recommendations for optimal sensor design to ensure reliable activation at all impact angles. Methods: The study used a combined approach to address the problem. Dynamic equations of the all-ways action mechanism were solved using the Runge-Kutta method, the magnetic field was simulated with FEMM 4.2 software, and the Hall voltage variation over time was analyzed to assess the fuse’s sensitivity under grenade impact conditions. Results: The results show that an activation threshold below 80 mV ensures reliable operation at any impact angle with an impact velocity not greater than 2.5 m.s-1. The mass of the inertial object has a significant impact on the sensitivity, more than the mass of the magnet, and the location of the Hall sensor is critical, with some locations providing stable sensitivity and others resulting in poor performance. Conclusion: The hybrid method presented in this paper effectively studies the signal from an electro-mechanical impact sensor combining an all-ways action mechanism, permanent magnets, and a Hall sensor. The research results are useful contributions to the design of impact sensors in grenade fuzes.